Organizational trust : a cultural perspective - Saunders, Mark, 1959- (Cambridge companions to management, 2010)
"The globalized nature of modern organizations presents new and intimidating challenges for effective relationship building. Organizations and their employees are increasingly being asked to manage unfamiliar relationships with unfamiliar parties. These relationships not only involve working across different national cultures, but also dealing with different organizational cultures, different professional cultures and even different internal constituencies. Managing such differences demands trust. This book brings together research findings on organizational trust-building across cultures. Established trust scholars from around the world consider the development and maintenance of trust between, for example, management consultants and their clients, senior international managers from different nationalities, different internal organizational groupings during times of change, international joint ventures, and service suppliers and the local communities they serve. These studies, set in a wide variety of national settings, are an important resource for academics, students and practitioners who wish to know more about the nature of cross-cultural trust-building in organizations"--Provided by publisher.